Taking on the Grand Trunk: The Locomotive Engineers Strike of 1876-7 - Morton, Desmond (Labour / Le Travail, 1977)
Examines the Locomotive Engineers strike of 1876-77 against the Grand Trunk Railway of Canada, the reaction of the company and the government. Argues that the strike set an important precedent for successful job action. Concludes that the polarizing nature of strikes forces people and governments to choose sides in labour conflicts.